Characterization of floating wastes along Manila Bay - Casibua, Angelica Lou D.; Lim, Athena Bernice J.; Tanchuling, Maria Antonia N.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Water pollution, most especially in Metro Manila, has become a serious problem in the country because of the harm it may bring to humans, animals and plants. Accordingly, solid wastes from Manila Bay will be a huge setback in the operations of the structures nearby. The study focuses on floating solid wastes in Manila Bay in the frontage of Manila Army and Navy Club, which is being retrofitted into five-star boutique hotel. These wastes were quantified and characterized in order to design and develop an effective waste collection system. Identification of the possible sources of these wastes and their movement patterns were also identified and analyzed. The methodology includes reviewing documents, doing frequent site visits and monitoring, and waste quantification and characterization. Upon evaluation, the most effective collection system is like a trawler mechanism. It includes two boats with net in-between. The net must be 4-mm and made up of permeable material. The time for collection depends on tide times and predominant longshore current direction. Good location points depend on seasonal wind regimes.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Marine debris -- Philippines -- Manila Bay